Access to the evidence base from general practice: a survey of general practice staff in Northern and Yorkshire Region. Issue 2 (1st June 2001) - Wilson, P; Droogan, J; Glanville, J; Watt, I; Hardman, G
Abstract : Aim —To identify and describe current methods of making health related research evidence accessible to general practice staff in the Northern and Yorkshire Region. Method —A postal survey questionnaire of general practice staff in the Northern and Yorkshire Region. Results —At least one completed questionnaire was obtained from 70% of the general practices surveyed, and the individual response rate to the survey was 45%. Just under 60% of all respondents reported having no access to the NHS internet and just under 50% also reported having no access to the internet. All respondents in this survey reported greater access to paper based information than to electronic databases. However, this research provides evidence of differential access to information resources between different professions in general practice with GPs clearly having easier access than other professions to both paper based resources and electronic databases. 70% of all respondents said that they would need to be trained to use either a computer, the internet, or to search databases if the opportunity for easy access to any of these information services was available. Conclusions —At the time of this survey, general practices seemed to be struggling to set up the infrastructure and develop the skills that are necessary to make best use of available research evidence. In addition, there is a need for further investigation into the reasons why different professions working in the same practice setting have differential access to information resources available in primary care.